Impact of mother tongue on construction of notes and first-year academic performance - Dukhan, Shalini; Cameron, Ann; Brenner, Elisabeth (South African Journal of Science, 2016)
The purpose of this study was to identify whether there are any differences in the quality of the notes constructed in English between students for whom English is a first language and those for whom it is a second language. Subsequently we assessed whether this difference, if any, affected their grades. Unsurprisingly, the first-language students produced better structured and more detailed notes; they also performed better academically than their second-language peers. However, when students were provided with training that focused on using writing as a means to promote critical thinking, there was an improvement in the personalisation of their notes. The improvement in grades was significant for second-language students. Thus the university has a pivotal role to play in preparing students for academic success by providing them with supportive measures to aid their transition into first year.Significance: • The work illustrates that writing can be used as a tool for students to improve their learning and their academic performance.• Second-language students’ grades improve when writing interventions are provided early in the year.• Students need to take on the responsibility for their learning; lecturers also have a responsibility in scaffolding learning.